TRANSMISI HADIS DAN MISTERI ‘AN - Nur, Imamul Authon (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
Indeed, Hadist in secundar book of hadith consist of 4 kinds they are: matan, sanad, rawi and symbol of transfer hadith. The experts of hadith paid attention against these symbols because the research of the symbols gave information about sanad condition between connected or not. After research about transfer hadith methods, from many imam?s books in ulumul hadith, the writer got that methods which used by rawi are limited eight methods. They are sam??, ar?, ijazah, mun?walah, muk?tabah, i?l?m, wa?iyah and wij?dah. The writer thought that the symbol ?an not from eight methods mentioned. It caused the difference about its result between connected or not. Some of the experts hadith thought that it is not connected. Most of the experts hadith thought it is connected with two requirements the first, the rawi must be safe of tadlish. The second, meeting of mu?an?in and mu?an?an ?anhu.